2015
DOI: 10.1016/j.geoforum.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

‘Seeing red’ in national parks: How visitors’ values affect perceptions and park experiences

Abstract: People's reasons for visiting national parks have been well researched. So too have their park activities and how diverse activities potentially affect visitors' park experiences (e.g. perceptions of overcrowding). Far less research has examined how park users' environmental values might affect their perceptions of other users and the appropriateness of different activities-a potential source of conflict. Relationships between personal environmental values and environmental and social perceptions are complex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 97 publications
2
37
0
2
Order By: Relevance
“…Source : [8] In the beggining of the exploration research about tourism motivation for vacation, identified some basic motivation dimension, for instance socio-pshycology, prestige, cultural, social, education, and benefit. The following research simplifies the number of motivation into four main domains that are climate or environment, relaxation or escape, adventure, dan personal [14,16].…”
Section: Push Factors : Motivationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Source : [8] In the beggining of the exploration research about tourism motivation for vacation, identified some basic motivation dimension, for instance socio-pshycology, prestige, cultural, social, education, and benefit. The following research simplifies the number of motivation into four main domains that are climate or environment, relaxation or escape, adventure, dan personal [14,16].…”
Section: Push Factors : Motivationsmentioning
confidence: 99%
“…Perception of someone's experience related to his feel involves between experience from surrounding environment stimulant and followed by activity as a responses or answer from the stimulant [18]. Perception refers to how human feels, processes mentally and acts to the information that received from surrounding environment [8].…”
Section: Pull Factors: Perceptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is difficult to determine whether there is a relevant dependency between visitor numbers and highly unstable spatial variables. Meta-analyses of the recreational value of national parks with respect to biophysical, socioeconomic and regional or national dummy variables document only a few dependencies, which are, furthermore, of low significance [32][33][34][35][36][37][38][39]. The chief limiting factor of this study, therefore, is the limited number of factors under examination.…”
Section: Discussionmentioning
confidence: 97%
“…This is true particularly for the deep Dyje river valley in the Podyjí National Park. It is therefore of interest to what extent this increased publicity translated into an increase in visitor numbers, and thus into economic benefits for local communities [32]. In Austria, the attendance of the Donau-Auen National Park remains singularly unaffected by the proximity of Vienna.…”
Section: Discussionmentioning
confidence: 99%